Risk-Based Audits to Reduce Water Loss (NRW) in PDAM Companies in Supporting Good Corporate Governance - fauzi, muchlis; Juanda, Ahamd; Leniwati, Driana (International Journal Labs, 2025)
Risk-Based Audit to Reduce Water Loss (NRW) at PDAM Giri Tirta, Gresik Regency, is an important approach to supporting sustainable Good Corporate Governance (GCG). This study explores the use of risk-based audits at PDAM Giri Tirta in Gresik Regency to reduce Non-Revenue Water (NRW) and support Good Corporate Governance (GCG). The findings show that risk-based audits are effective in identifying water loss, improving operational efficiency, and enhancing the company's financial and governance practices. This research is designed as a case study of qualitative methods to analyze the implementation of risk-based audits in PDAM Giri Tirta, Gresik Regency. Primary data was obtained through interviews with the general director, the director of the Internal Control Department, the meter recording section, and the accounting section. In contrast, the secondary data was composed of financial documentation. The results show that the water leakage rate is still high, but risk-based audits can help identify and reduce water loss and improve the operational efficiency of PDAMs. The theoretical implication of this study is a paradigm shift in auditing towards a risk-based approach, while it can practically help PDAM companies manage risks and improve operational performance.